Предоставление муниципальных услуг в условиях функционирования в режиме "повышенная готовность" - Огородников, Александр Константинович (Перспективы развития фундаментальных наук. Т. 5 : сборник научных трудов XIX Международной конференции студентов, аспирантов и молодых ученых, 26-29 апреля 2022 г.)
This article analyzes the functioning of the local government in terms of the provision of municipal services in the field of land relations. Based on the analysis, the main trends in changes in the conditions for the provision of municipal services in connection with the introduction of the "hich readness mode " on the territory of a constituent entity of the Russian Federation were identified. The author suggests ways to improve legislation on this issue.